Modernist Poetic Practices in English Poetry from Southeast Asia: A Comparison Between Jose Garcia Villa and Arthur Yap - Patke, Rajeev S. (Archīum Ateneo, 2024)
The paper develops a comparison between Jose Garcia Villa (1908-97) and Arthur Yap (1943-2006) as the principal Modernists of English poetry from Southeast Asia. Though they wrote from very dissimilar backgrounds, and in very different circumstances, each represents for his time and place a radical assimilation of Western poetic practices into a new form of experimental writing. The comparison delineates the various ways in which their example reveals the scope and limits of what can be achieved through a systematic subversion of traditional modes of poetic writing in Southeast Asia.